Reserved election: Boost for multiracialism? - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2016)
Singapore is on the threshold of the most significant re-engineering to its constitutional architecture since the introduction of the Elected Presidency (EP) in 1991.